Impacts of Covid-19 Lockdown in the Academic Life of Undergraduate Students: An Online Survey - Pandey, Akash; Gurung, Pooja (Nepal Journal of Multidisciplinary Research, 2021)
The impact of COVID-19 lockdown can be widely observed in all sectors of the nation including education. An online survey was conducted to identify the impacts brought by the nationwide lockdown in the academic life of undergraduate students currently studying at different bachelor's levels and the ones who have completed final exams after the ease of lockdown. Particularly, the study explored both the positive and negative impact of COVID-19 lockdown. A structural questionnaire link using ‘Google form’ was circulated using messenger and E-mail from 20 April to 27 April 2021. A total of 98 students, from Tribhuvan University (60), Kathmandu University (16), Pokhara University (11), and Purbhanchal University (11) participated in the survey. The study found that around 42.86% of the students' academic life was affected negatively whereas only 2.04% reported positively. The majority of students pointed to delay in examinations as the primary negative impact followed by difficulty in learning due to excessive use of the internet, disturbance in pass out the pattern, loss of job, and issues of dropout. On the positive side, students have experienced an improvement in reading habits, development in the skills of self-study, virtual learning, group work, and digital competencies. Thus, the study concludes that students' academic life was impacted negatively than positively. Therefore, the study suggests universities, educational institutions, and relevant stakeholders come up with a concrete plan to respond to the impacts seen in the academic career of students unless the lockdown perpetuates other consequences.